Lipidomics Analysis of the Tears in the Patients Receiving LASIK, FS-LASIK, or SBK Surgery - Gao, Yan; Qi, Yuanyuan; Huang, Yue; Li, Xiaorong; Zhou, Lei; Zhao, Shaozhen (Frontiers in Medicine, 2021)
Purpose: Tear film lipid layer (TFLL) plays a vital role in maintaining the tear film stability and, thus, the lipid composition of the tears could greatly affect the physiological function and biophysical integrity of the tear film. The objective of this study is to assess the tear lipid composition of the patients receiving laser-assisted in situ keratomileusis (LASIK), femtosecond LASIK (FS-LASIK), or sub-Bowman's keratomileusis (SBK) surgery preoperatively and postoperatively. Methods: Tear samples were collected from the left eye of the patient who receiving LASIK (n = 10), FS-LASIK (n = 10), or SBK (n = 10) surgery in week 0, week 1, week 4, and week 52. A rapid direct injection shotgun lipidomics workflow, MS/MSALL (<2 min/sample), was applied to examine the tear lipidome. Results: In week 52, the SBK group demonstrated a similar lipidome profile compared to week 0, while the FS-LASIK and LASIK groups shifted away from week 0. Two lipids, ganglioside (GD3) 27:4 and triacylglycerol (TAG) 59:3, were found to be associated with the lipidome changes preoperatively and postoperatively. No statistical significance was found in the overall lipid classes from the FS-LASIK group. The LASIK group showed significant alteration in the phospholipid and sphingolipid over time, while the SBK group demonstrated a significant difference in the (O-acyl)-ω-hydroxy fatty acid (OAHFA) and phospholipid. Conclusion: LASIK showed the greatest impact on the tear lipidome changes over time, while SBK demonstrated minimal impact among the three types of refractive surgeries after 1 year.